Comparative Study of the Use of Video-Based Learning Media and Textbooks on Fiqh Learning Outcomes - Ahmad Maulana Ashrafi; Rofiatul Hosna (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study examines the comparative use of video-based learning media and textbooks on the learning outcomes of Fikih students in grade XI at SMK Diponegoro Ploso Jombang. This study uses a quantitative research design with a true experimental design. The data analysis techniques in this study use several tests, namely the classical assumption test, the one-sample t-test, and the two-sample t-test.” The results of the one-sample t-test for variables X1 and Y show that t_calculated 2.682 > t_table 2.060 and the significance value 0.013 < 0.05. Therefore, it can be concluded that H0 is rejected and Ha is accepted. For X2 and Y, it was found that t_calculated 0.165 < t_table 2.060 and the significance value 0.870 > 0.05. Therefore, it can be concluded that H0 is accepted and Ha is rejected. X1 and X2 on Y, it is known that t_calculated 2.677 > t_table 2.008 and the significance value 0.010 < 0.05. Therefore, it can be concluded that H0 is rejected and Ha is accepted. From the comparison test results, there is a comparison between the use of video-based media and textbooks on the learning outcomes of Fikih students in grade XI at SMK Diponegoro Ploso Jombang.